1991
DOI: 10.3171/jns.1991.74.5.0701
|View full text |Cite
|
Sign up to set email alerts
|

Management of chiasmal and hypothalamic gliomas of infancy and childhood with chemotherapy

Abstract: Between March, 1983, and February, 1989, 19 infants or children with chiasmal/hypothalamic gliomas were treated with chemotherapy after either surgical or radiological diagnosis. The patients ranged in age from 15 weeks to 15.6 years (median 3.2 years) at the start of therapy. Twelve patients were treated immediately after diagnosis because of progressive symptoms, and seven received chemotherapy after either radiographic progression or clinical deterioration, including progressive visual loss or intracranial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
82
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(83 citation statements)
references
References 44 publications
1
82
0
Order By: Relevance
“…Temozolomide has also been shown to be useful in stabilizing disease in more than 50% of patients without significant toxicity 26 and is considered an option in patients with progressive OPG in whom first-line therapy has failed. Petronio et al 67 addressed the use of a 5-drug regimen consisting of 6-thioguanine, procarbazine, dibromodulcitol, lomustine, and vincristine for treatment of OPG, and they obtained favorable results. A similar regimen in which dibromodulcitol was excluded was compared with the standard regimen of carboplatin and vincristine in 2003 and was deemed a reasonable second-line therapy for patients with OPG.…”
Section: Chemotherapy For Opgsmentioning
confidence: 99%
“…Temozolomide has also been shown to be useful in stabilizing disease in more than 50% of patients without significant toxicity 26 and is considered an option in patients with progressive OPG in whom first-line therapy has failed. Petronio et al 67 addressed the use of a 5-drug regimen consisting of 6-thioguanine, procarbazine, dibromodulcitol, lomustine, and vincristine for treatment of OPG, and they obtained favorable results. A similar regimen in which dibromodulcitol was excluded was compared with the standard regimen of carboplatin and vincristine in 2003 and was deemed a reasonable second-line therapy for patients with OPG.…”
Section: Chemotherapy For Opgsmentioning
confidence: 99%
“…A variety of drugs have been used, including vincristine, actinomycin D, etoposide, carmustine, and carboplatin, as well as combination regimens consisting of these drugs (R. Prados, personal communication, 1996). [5,14,17,18,20,21,24] In 1989, a study was begun to evaluate the efficacy of combining carboplatin and vincristine in treating children with recurrent and newly diagnosed astrocytomas. The objective response rates of 60 children, including 37 with newly diagnosed astrocytomas, have been reported.…”
mentioning
confidence: 99%
“…These pilot trials reported regression or stability of tumors in 75-90% of patients. [82][83][84] At follow-up, children treated on the carboplatin/vincristine regimen before age 5 years, had a 75% 4-year PFS rate. 85 The outcome of a recently-closed COG phase III randomized trial comparing the latter two of these regimens is pending.…”
Section: Gliomas/astrocytomasmentioning
confidence: 99%